2019
DOI: 10.1007/s00702-019-02126-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of gamma–delta relationship related to working memory deficits in first-episode psychosis

Abstract: Working memory (WM) deficits constitute a core symptom of schizophrenia. Inadequacy of WM maintenance in schizo-phrenia has been reported to reflect abnormalities in the excitation/inhibition (E/I) balance between pyramidal neurons and parvalbumin basket cells, which may explain alterations of the dynamics of gamma and delta oscillations. To address this issue, we assessed event-related gamma (35-45 Hz) and delta (0.5-4 Hz) oscillatory responses in a visual n-back WM task in patients with first-episode psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…In one study, FES subjects, as compared to HCs, had a decrease in the occurrence of anterior–to-posterior propagation of delta waves during auditory and visual tasks ( 82 ). A second study, carried out in FEP subjects, demonstrated a workload-dependent increase of the duration of delta oscillations during a working memory task ( 81 ) not observed in HCs. This was revealed by longer delta oscillation cycles in FEP during the performance of tasks of increasing difficulty.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In one study, FES subjects, as compared to HCs, had a decrease in the occurrence of anterior–to-posterior propagation of delta waves during auditory and visual tasks ( 82 ). A second study, carried out in FEP subjects, demonstrated a workload-dependent increase of the duration of delta oscillations during a working memory task ( 81 ) not observed in HCs. This was revealed by longer delta oscillation cycles in FEP during the performance of tasks of increasing difficulty.…”
Section: Resultsmentioning
confidence: 90%
“…Three studies investigated delta activity while subjects performed a task ( 81 83 ). In one study, FES subjects, as compared to HCs, had a decrease in the occurrence of anterior–to-posterior propagation of delta waves during auditory and visual tasks ( 82 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[21][22][23][24][25][26] Similarly, research also shows that qEEGderived frequency bands, microstate analysis, and event-related oscillations (EROs; non-phase locked rhythmic pattern of neural activity) are highly modified in pathological brains. [27][28][29][30] Despite encouraging data, the relevance of such tools in daily psychiatric clinics is still under investigation. Second, at a therapeutic level, it is worth noting that noninvasive brain stimulation (NIBS) that utilizes neuroelectric principles to modulate brain activity (such as transcranial direct current stimulation [tDCS], transcranial alternating current stimulation [tACS], or transcranial magnetic stimulation [TMS]) have been successfully established for the treatment of a wide range of psychiatric disorders (for a review, see Lefaucheur et al 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…• EROs: The study of EROs enables the measurement of frequency-specific brain electrical oscillations in neural circuits that are related to the sensory and cognitive processing of stimuli. 88 EROs are commonly classified according to the "natural frequencies" of the brain, 89 that is, delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-70 Hz). The analysis of EROs yields several measures such as event-related power, event-related phase locking (intertrial coherence), event-related coherence, and cross-frequency coupling.…”
mentioning
confidence: 99%